PEMANFAATAN TEKNOLOGI DIGITAL MARKETING DAN PACKAGING PRODUK TUJUAN EKSPOR UMKM KABUPATEN GRESIK - Gugus Wijonarko; Arisanti, Dian; Panca Rahardiyanto (DedikasiMU : Journal of Community Service, 2025)
Usaha Mikro Kecil dan Menengah (UMKM)) UD Ridho Illahi is a productive individual business based on the creative economy in Gresik Regency as one of the UMKM under the guidance of Asosiasi Gabungan Pengusaha Eksportir Indonesia (GPEI) which is hampered in its development due to various factors. The root of the problem lies in the absence of training and the lack of maximum assistance, especially in the field of digital-based marketing and product packaging development. The limitations of UMKM in terms of knowledge and skills in utilizing digital platforms to reach wider consumers and design attractive product packaging that meets international standards. For this reason, assistance and training are needed to improve the quality of products and their marketing by utilizing technology, namely digital printing technology and digital marketing technology and creative packaging. Assistance and training are carried out consistently and continuously supported by the Grant program from Higher Education. Stiamak maps the conditions and problems faced by the UMKM question to then provide solutions to these problems. A series of community service programs start with training that includes the Canva business model, digital marketing, and attractive packaging in the context of exports. These trainings are expected to improve the quality of business planning bases and market expansion. The craftsmen can receive training materials easily and enthusiastically. Furthermore, to realize the program, it is necessary to follow up with the handover of Ecoprint production equipment assistance to increase craftsmen’s productivity. The sustainability of the program so that it runs well is carried out by post-training assistance and control to monitor and improve the results of the training so that this program has a significant effect with the hope that ecoprint products can enter the export market.